Getting Lost: Photographs from Jonathan Johnson's Low Season and Green Country. Issue 4 (2nd October 2018) - Harnetty, Brian
Abstract : This essay explores Jonathan Johnson's recent photographic works in Thailand and Costa Rica, where he uses methods of walking and getting lost to critically address productivism and the speed and consumption of digital culture. Richly contextual, the images explore themes of urban and rural landscapes, absence and presence, and in-betweenness. Throughout, Johnson draws from his experiences of moving between cultures, places, and his Thai and American heritage.